Mapping mental health recovery tools developed by mental health service users and ex-users: protocol for a scoping review - Hernán María Sampietro; Viviana R Carmona; J Emilio Rojo; Juana Gómez-Benito (BMJ Open)
Introduction Since the emergence in 1997 of the Wellness Recovery Action Plan, a number of other tools developed by users and/or ex-users of mental health services have been published and implemented. All these tools aim to promote self-determination in mental health recovery processes. A scoping review will be carried out in order to (1) identify existing tools, (2) describe their distinctive characteristics and (3) examine how they have been implemented and evaluated.Methods and analysis The scoping review will be guided by the methodological framework proposed by Arksey and O’Malley and expanded by Levac et al. It will involve, primarily, a literature search of the following electronic databases: Cochrane database, Cumulative Index to Nursing and Allied Health Literature, PsycInfo, PsycArticles, Scopus, PubMed and Web of Science. In addition, the search process will consider grey literature databases. Users, ex-users and survivors organisations and networks will be contacted in order to identify any relevant material. The reference lists of the articles identified through the literature search will be inspected. Finally, hand searches of journals will be conducted in order to increase the confidence in the search. Two main approaches will be used to present the charted data: a descriptive analysis and a thematic analysis. The study will be performed between April and December 2020. The results will be reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews.Ethics and dissemination This study does not require ethical approval because the data used are from publicly available materials. The study results will be disseminated through an article submitted for publication to a scientific journal and presented at relevant conferences. The results will also be shared in future workshops and seminars as part of continuing education programmes for mental health professionals.